Leadership and Vision: Evolving Strategies - Kandy Dayaram
I n s p i t e o f c h a n g e i n i t i a 123456 tives proposed at state level, the question of the 123456 123456 p r o c e s s e s o f r e f o r m a t i o 123456 n and redress within the South African education 123456 123456 123456 l a n d s c a p e r e m a i n s o b s c u 123456 re. The potential for linking leadership and strategy 123456 123456 t o d e b a t e s a b o u t c o n s e 123456 n sus and divergence of transformation policies and 123456 123456 123456 p r o c e d u r e s , p o s e s a m a j o r c h a l l e n g e t o t h 123456 e facilitators of the change mechanisms, par ticularly 123456 123456 123456 a f t e r a d e c a d e o f S o u t h A f r i c a a c h i e v i 123456 n g democracy. This paper assesses the evolving 123456 123456 s t r a t e g i e s o f t r a n s f o r m a t i o n a l p r o g r e s s w 123456 i t h 123456 p a r t i c u l a r f o c u s o n t h e p r o s p e c t i v e p r o c e s s e s 123456 123456 w h i c h m a y a s s i s t k e y p o l i c y m a k e r s a n d e 123456 xecutors to move towards effective public service 123456 123456 123456 delivery, nationally and globally.